2022
DOI: 10.1055/s-0041-1742091
|View full text |Cite
|
Sign up to set email alerts
|

What We Know (and Do not Know) Regarding the Pathogenesis of Pulmonary Thrombosis in COVID-19

Abstract: The clinical course of coronavirus disease 2019 (COVID-19) is often complicated by the onset of venous thrombosis and thromboembolism (VTE), encompassing also pulmonary thrombosis. Recent statistics attests that the cumulative frequency of VTE can be as high as 30% in COVID-19 hospitalized patients, increasing to nearly 40 to 70% (depending on systematic screening) in those with severe illness, mechanical ventilation, or intensive care unit admission. The risk of venous thrombosis seems mostly limited to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The identification of APS requires both the presence of clinical evidence of thrombosis or pregnancy/fetal morbidity, as well as laboratory evidence of presence of aPL. For the former, thrombosis is already a feature of severe COVID-19 through multiple pro-thrombotic mechanisms [ 78 , 79 , 80 , 81 , 82 ], so this confounds the clinical evidence required to identify APS. For the latter, aPL are present in a proportion of asymptomatic patients (potentially up to 5% of the general population may be positive in one or more aPL tests).…”
Section: Autoantibodies Interfering With Hemostasis In Covid-19 and A...mentioning
confidence: 99%
“…The identification of APS requires both the presence of clinical evidence of thrombosis or pregnancy/fetal morbidity, as well as laboratory evidence of presence of aPL. For the former, thrombosis is already a feature of severe COVID-19 through multiple pro-thrombotic mechanisms [ 78 , 79 , 80 , 81 , 82 ], so this confounds the clinical evidence required to identify APS. For the latter, aPL are present in a proportion of asymptomatic patients (potentially up to 5% of the general population may be positive in one or more aPL tests).…”
Section: Autoantibodies Interfering With Hemostasis In Covid-19 and A...mentioning
confidence: 99%
“…13 As far as the onset of thrombotic episodes during SARS-CoV-2 infection is concerned, either localized or systemic, several lines of evidence now attest that such risk is considerably spotted and multifaceted. 14 A recent meta-analysis of 21 studies, totaling 5,296 patients, reported a significantly increased risk of VTE in patients with elevation of some well-known laboratory biomarkers such as D-dimer, troponin, and C-reactive protein (CRP), as well as with overall length of hospitalization, intubation, and inotropic drugs requirement, while no substantial associations were found with other conventional risk factors such as personal history of thrombosis, cancer, and overweight. 15 These results could be confirmed in another study, which concluded that the risk of PE was nearly 60% higher in males, nearly fourfold higher in patients needing mechanical ventilation, and threefold higher in those admitted to the ICU.…”
Section: Tablementioning
confidence: 99%
“…2 An increased risk of developing acute thrombotic evens, both venous and arterial, is a hallmark of severe/critical COVID-19 cases, as comprehensively described elsewhere. [3][4][5] Thus, D-dimer values are very frequently elevated in patients with SARS-CoV-2 infection, correlate with the clinical phenotype, and predict the risk of developing thrombosis and multiple organ failure. 6,7 It is hence not surprising that the number of D-dimer test requests may have undergone a paramount increase throughout the COVID-19 pandemic, whereby the value of this biomarker may provide a valuable, almost unreplaceable contribution to the diagnostic approach, clinical decision making, risk stratification and managed care of patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%